Maritime Links Between China, Sumatra, the Malay Peninsula, and Buddhist Monasteries in India (c. 11th–12th Centuries) in the Light of Two Fragmentary Inscribed Strips of Copper from Muara Jambi - Wahyu Rizky Andhifani; Hedwi Prihatmoko; Andrea Acri; Arlo Griffiths; Mathilde Mechling; Gregory Sattler (Religions)
This article explores the maritime connections relating to Buddhism and diplomacy between polities in Sumatra, the Malay Peninsula, the Indian subcontinent, and China from the beginning of the 11th century up to the 12th century CE. It focuses on new epigraphic evidence from Muara Jambi in the form of two inscribed strips of copper mentioning the Cūḍāmaṇivarmavihāra, a monastery funded by the king of Śrīvijaya in Nagapattinam (South India), and the Bālādityavihāra, probably located in Nālandā (Northeastern India). These new findings are compared to archaeological and textual materials from elsewhere in the Buddhist world that cast light on the web of transregional connections between Nusantara, China, and India in the early centuries of the second millennium.